Expert-analytical Support of Foreign Policy Activities - A. A. Varfolomeev; O. P. Ivanov; I. V. Surma; Y. A. Trefilova (Vestnik MGIMO-Universiteta)
The article presents the final results of the project studying the system of expert and analytical support for foreign policy decisions. The project is devoted to conducting a survey and a set of interviews with employees of government bodies (leaders and chief specialists) who are involved in the process of preparing and making foreign policy decisions. The article contains the officials’ assessment of the main challenges when interacting with the scientific and expert community, as well as a "desired image" of such interaction.The study was held in two stages (stage I in February-October 2020, stage II-in January-August 2021) in the form of a survey with a set of follow-up interviews for a more detailed interpretation of the data obtained. The interviewees included 24 employees of federal executive bodies (the Ministry of Foreign Affairs of Russia and Rossotrudnichestvo; departments of international cooperation of line ministries, agencies and services); offices of the chambers of the Federal Assembly of the Russian Federation (departments providing international and inter-parliamentary cooperation). All participants of the study are in positions of the "managers" category or are part of the group of "chief specialists", that is, they have experience in decision-making process and/or in elaborating them. The survey and interviews were anonymous. The research is within structural-functional, institutional and regulatory approaches. The authors note that informational materials with low level of generalization and lacking recommendations and forecasts will never replace genuine analytics and expertise. Given the development of artificial intelligence, generalizing information will be automatized. As a result, expertise has to be of better quality.